2019
DOI: 10.1140/epjc/s10052-019-6727-2
|View full text |Cite
|
Sign up to set email alerts
|

Weak-field limit and regular solutions in polynomial higher-derivative gravities

Abstract: In the present work we show that, in the linear regime, gravity theories with more than four derivatives can have remarkable regularity properties if compared to their fourth-order counterpart. To this end, we derive the expressions for the metric potentials associated to a pointlike mass in a general higher-order gravity model in the Newtonian limit. It is shown that any polynomial model with at least six derivatives in both spin-2 and spin-0 sectors has regular curvature invariants. We also discuss the dynam… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
51
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 117 publications
(408 reference statements)
6
51
1
Order By: Relevance
“…For regularity properties of higher derivative gravity theories which contain at least six derivatives, see[56,57] 11. We would like to thank the referee to bring this point to our attention.…”
mentioning
confidence: 99%
“…For regularity properties of higher derivative gravity theories which contain at least six derivatives, see[56,57] 11. We would like to thank the referee to bring this point to our attention.…”
mentioning
confidence: 99%
“…Now considerφ(s) defined bỹ where we again assume that the contour could be closed to encircle all of poles. Then using the Cauchy residue theorem 13 we havẽ…”
Section: Calculation Of the Tracementioning
confidence: 99%
“…By the inverse Mellin transform (C.4), we can write for small t Once again being sloppy about the contour and not pretending to be rigorous we can read of poles of Γ(s)ζ P (s): Res(Γ(s)ζ P (s))| s= d−n m = a n (P ) . (C.19) 13 Here by χ (k) we denote in a standard way the k-th derivative of the cut-off function with respect to its argument p: χ (k) = d k χ(p) dp k .…”
Section: Calculation Of the Tracementioning
confidence: 99%
“…Just as in general relativity [27], Schwarzschild spacetime is a stable solution in NLG at the linear level. Whether this solution also represents an actual, astrophysical black hole remains to be seen, since approximated solutions of the linearized equations of motion (EOM) look regular [28][29][30][31][32][33]. More recently, in [34] it was found that the NLG dynamics of small perturbations of Minkowski metric is the same as in Einstein gravity.…”
Section: Introductionmentioning
confidence: 99%